Enhanced Performance of the 4 × 20 Gbit/s-40 GHz OFDM-Based RoFSO Transmission Link Incorporating WDM-MDM of Hermite Gaussian and Laguerre Gaussian Modes - Singh, Karamjeet; Singh, Mehtab; Grover, Amit; Miglani, Rajan; Singh, Harjeevan; Amhoud, El Mehdi (Frontiers in Physics, 2022)
A 4×20Gbit/s-40GHz orthogonal frequency-division multiplexing-based radio-on-free-space optics information link integrating hybrid wavelength- and mode-division multiplexed transmission techniques is proposed in this paper. Furthermore, an ameliorate detection scheme deploying a square-root-module after each photo-diode at the receiver terminal has been proposed to mitigate the adverse performance effects as a result of non-linear photo-diode characteristics. The results presented show a successful 80Gbit/s-160GHz transmission at 3000 m and 2700 m under heavy rainy and foggy weather respectively. The link demonstrates superior performance in terms of maximum range and transmission rate as compared to the previous works.